Thirteen steps for office hysteroscopy with minimal discomfort - Lasmar, Ricardo Bassil; Lasmar, Bernardo Portugal (Clinical Journal of Obstetrics and Gynecology, 2019)
The Office hysteroscopy (OH) is a important procedure to make diagnosis and sometimes, treatment, of intrauterine pathology, without getting the patient to Operating Room. Its advantages are very well known: less costs, fast diagnosis, see and treat and several others. It’s mainly difficulty is the discomfort during the procedure. To stimule to grow the number of gynecologist to leave OR and to go to office hysteroscopy, we propose thirteen steps for office hysteroscopy with minimal discomfort